Cryptosporidium-host Interaction alters regulation of oncomiRNAs and tumor suppressor miRNA expression - Başak, Feyza; Jainul, Mohammed Abdullah; Mat Yusof, Afzan (Asian Network for Scientific Information, 2019)
The apicomplexan parasite Cryptosporidium is well-known for its capability to induce cryptosporidiosis, a severe diarrheal disease in human and animals. Cryptosporidium can also be a potential pathogen in human for cancer progression, particularly colorectal cancer. This review was designed to outline the information about the life cycle of the Cryptosporidium, the consequences of Cryptosporidium infection into the response mechanism in immune compromised host and finally the regulation of oncomiRNAs and tumor suppressor miRNAs upon Cryptosporidium infection. Host-Cryptosporidium interaction caused alteration of expression of a series of microRNAs or miRNAs as a result of controlling defense mechanism. Regulation of miRNAs in the infected cells may be identified as possible biomarkers in cancer progression. Upregulation of oncomicroRNAs or oncomiRNAs and the downregulation of tumor suppressor miRNAs in the host epithelial cells due to the Cryptosporidium infection may lead to cancer initiation on human.